Complicaciones inmediatas y mediatas de fracturas por perdigones según clasificación de Gustilo y Anderson en el Hospital Regional de Loreto enero 2018 - diciembre 2020 - Ruiz Isminio, Juan Eli (2023)
Objectives: To determine the association between immediate complications of pellet fractures in relation to the Gustilo and Anderson classification in patients treated at the Regional Hospital of Loreto during the period from January 2018 to December 2020. Methods: observational, descriptive and cross-sectional design of patients older than 18 years with a diagnosis of pellet fractures. Results: 78 patients were registered, 96.2% being male, with a mean age of 35 years. Fifty percent presented multiple fractures; 30.8% were hospitalized in less than 24 hours; 84.6% were classified as Gustilo and Anderson type III A; and 25.6% presented immediate complications. The tibia was the most affected body part (21.8%); the most frequent treatment was surgical cleaning (87.2%), followed by fixation with plate and screw (16.7%). Infection was the most frequent complication (17.9%), 9% presented anemia acute and 3.8% hemothorax or pneumothorax. Acute anemia was the complication that was statistically associated with the Gustilo and Anderson classification with significance (p <0.002). Conclusions: It is concluded that there is a statistically significant association between anemia as a complication and the Gustilo and Anderson classification, in patients treated at the Regional Hospital of Loreto.